PENDIDIKAN AGAMA KRISTEN DAN IMPLIKASINYA DALAM PEMBENTUKAN KARAKTER ANAK DI ERA TEKNOLOGI INTERNET - Desi Karo Karo (Jurnal Excelsior Pendidikan, 2021)
Abstract: The world of children becomes the world of the internet so that the dominant learning is driven by internet knowledge. This study examines the nature and role of Christian religious education in the formation of children's character in the era of internet technology. The literature research used to examine various data sources concludes that: (1) Religious learning is the door to changing children's character according to the Bible. (2) The role of education: (a) forming children: towards spiritual maturity in Christ Jesus, in agape education, love, and righteousness. (b) The role of fathers and mothers: leading their children to live in groups, setting an example and educating, educating children according to bible teachings, disciplining children. (c) The role of the church: a place of change for its congregation, prepares the younger generation, is responsible for using internet technology, and is a doer of the word. (d) The role of schools: guiding and educating their students, able to understand, appreciate and believe in the greatness of God in their lives, able to transmit gratitude to God and act responsibly. (e) The role of the teacher: teaching God's Word, guiding and helping children use internet technology, increasing faith in Christ, giving advice, and teaching God's Word (representing God's love).Abstrak: Dunia anak-anak menjadi dunia internet, sehingga pembelajaran yang dominan didorong oleh pengetahuan internet. Penelitian ini mengkaji hakikat dan peran pendidikan agama Kristen dalam pembentukan karakter anak di era teknologi internet. Penelitian kepustakaan yang digunakan untuk mengkaji berbagai sumber data menyimpulkan bahwa: (1) Pembelajaran agama merupakan pintu untuk mengubah karakter anak sesuai dengan Alkitab. (2) Peranan pendidikan: (a)Â  membentuk anak: menuju kedewasaan rohani dalam Kristus Yesus, pada pendidikan agape, kasih dan benar.(b) Peran ayah dan ibu: memimpin anak-anaknya hidup berkelompok, memberi teladan dan mendidik, mendidik anak sesuai ajaran alkitab, mendisiplinkan anak. (c) Peran gereja: tempat perubahan bagi jemaatnya, mempersiapkan generasi muda, bertanggungjawab menggunakan teknologi internet, dan pelaku firman. Â (d) Peran sekolah: membimbing dan mendidik anak didiknya, mampu memahami, menghayati dan meyakini kebesaran Tuhan dalam hidupnya, mampu menularkan rasa syukur kepada Tuhan dan berbuat untuk bertanggungjawab. (e) Peranan guru: mengajarkan Firman Tuhan, membimbing dan membantu anak menggunakan teknologi internet, meningkatkan iman kepada Kristus, memberi nasihat dan mengajarkan Firman Tuhan (mewakili kasih Tuhan).Â